High-buffering, anti-falling and heat-insulating PE (polyethylene) film, preparation method thereof, composite film and bag

A three-layer PE film with foaming layers addresses thermal insulation and cushioning issues in drink packaging, ensuring prolonged temperature retention and drop resistance.

CN119189468AActive Publication Date: 2024-12-27JIANGMEN HUALONG MEMBRANE MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411349561.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-27
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

Current packaging for cold and hot drinks lacks thermal insulation, leading to rapid temperature changes and poor cushioning, making them uncomfortable to hold and prone to damage from drops.

Method used

A high-buffering, drop-resistant PE film composed of a three-layer co-extruded structure with at least one foaming layer, using specific polyethylene blends and foaming masterbatches to create a thermal insulation effect and cushioning properties.

Benefits of technology

The film provides enhanced thermal insulation, maintaining drink temperature for extended periods, offering comfort and protection against drops while maintaining structural integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005062776280000151
    Figure BDA0005062776280000151
  • Figure BDA0005062776280000161
    Figure BDA0005062776280000161
  • Figure BDA0005062776280000171
    Figure BDA0005062776280000171
Patent Text Reader

Abstract

The invention relates to the technical field of composite films, and provides a high-buffering, anti-falling and heat-insulating PE film, a preparation method thereof, a composite film and a bag. At least one of the outer layer, the middle layer and the inner layer of the high-buffering anti-falling heat insulation PE film is of a foaming structure, the foam holes can play a role in blocking cold and hot air, the unfreezing time of frozen drinks and the cooling time of hot drinks are prolonged, the hand feeling is comfortable, and the feeling of cold and hot hands is avoided; meanwhile, due to the foaming structure, the PE film has a buffering effect and is not easy to damage after falling off; in addition, the PE film provided by the invention is light in weight, good in flexibility, higher in appearance and better in customer experience. Furthermore, the invention also provides a specific formula of the three-layer structure of the high-buffering anti-falling heat-insulating PE film, and the formula is strictly controlled, so that the PE film can be ensured to have higher mechanical properties on the basis of obtaining compact cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite films, and in particular to a high-buffering, drop-resistant, heat-insulating PE film and a preparation method thereof, as well as a composite film and a bag. Background Art

[0002] Cold drinks are a type of beverage that is very popular among consumers in the summer and have a cooling effect; hot drinks are drinks with a certain temperature that are provided by boiling or brewing with hot water, such as tea, coffee, Chinese herbal health drinks, etc., and their unique flavor can usually only be enjoyed through hot drinks.

[0003] Cold drinks and hot drinks have certain temperatures. Some cold drink and hot drink packaging bags currently on the market have poor thermal insulation, especially cold drinks with ice melt quickly and feel cold; the temperature of hot drinks drops easily and is very hot when just held in the hand; at the same time, the current packaging bags have no cushioning and anti-drop performance, and are easily damaged after falling. Summary of the invention

[0004] In view of this, the present invention provides a high-buffered anti-drop heat-insulating PE film and a preparation method thereof, as well as a composite film and bag. The high-buffered anti-drop heat-insulating PE film provided by the present invention has excellent heat insulation and cold insulation effects, and has buffering properties, and is not easily damaged after falling.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] A high-buffering, drop-resistant and heat-insulating PE film is made of a three-layer co-extruded blown film of an outer layer, a middle layer and an inner layer; at least one of the outer layer, the middle layer and the inner layer is a foaming structure.

[0007] Preferably, the raw materials for preparing at least one of the outer layer, the middle layer and the inner layer include foaming masterbatch;

[0008] The foaming masterbatch has a melt index of 4-7 g / 10 min and a density of 0.913-0.955 g / cm 3 .

[0009] Preferably, when only the raw materials for preparing the outer layer include foaming masterbatch, the mass of the foaming masterbatch is 2 to 8% of the total mass of the raw materials for preparing the outer layer; when only the raw materials for preparing the middle layer include foaming masterbatch, the mass of the foaming masterbatch is 1.5 to 8% of the total mass of the raw materials for preparing the middle layer; when only the raw materials for preparing the inner layer include foaming masterbatch, the mass of the foaming masterbatch is 2 to 6% of the total mass of the raw materials for preparing the inner layer; when any two layers of the outer layer, the middle layer and the inner layer contain foaming masterbatch, or all three layers contain foaming masterbatch, the mass of the foaming masterbatch in each layer is 1 to 11% of the total mass of the raw materials for preparing the layer.

[0010] Preferably, the model of the foaming masterbatch is CFE-3361G and / or FM10PE.

[0011] Preferably, the raw materials for preparing the outer layer include, by weight: 10 to 60 parts of low-density polyethylene, 20 to 80 parts of linear low-density polyethylene, 15 to 60 parts of metallocene low-density polyethylene, 0 to 8 parts of foaming masterbatch, and 0.5 to 1.5 parts of processing aid;

[0012] The raw materials for preparing the middle layer include, by weight: 10 to 98 parts of low-density polyethylene, 0 to 8 parts of foaming masterbatch, and 0.5 to 1.5 parts of processing aid;

[0013] The raw materials for preparing the inner layer include, by weight: 15 to 50 parts of low-density polyethylene, 20 to 80 parts of metallocene low-density polyethylene, 10 to 80 parts of linear low-density polyethylene, 0 to 8 parts of foaming masterbatch, and 0.5 to 1.5 parts of processing aid;

[0014] In the raw materials for preparing the outer layer, the middle layer and the inner layer, the mass fractions of the foaming masterbatch are not all 0.

[0015] Preferably, the outer layer uses a low-density polyethylene with a melt index of 0.2-5 g / 10 min and a density of 0.920-0.935 g / cm 3 The outer layer adopts linear low-density polyethylene with a melt index of 0.3-3.5 g / 10 min and a density of 0.912-0.930 g / cm 3 The outer layer adopts a metallocene low-density polyethylene with a melt index of 0.5 to 2.5 g / 10 min and a density of 0.908 to 0.930 g / cm 3 ;

[0016] The low-density polyethylene used in the middle layer has a melt index of 0.1-3.5 g / 10 min and a density of 0.920-0.940 g / cm 3 ;

[0017] The low-density polyethylene used in the inner layer has a melt index of 0.3-3.5 g / 10 min and a density of 0.920-0.930 g / cm 3 The metallocene low-density polyethylene used in the inner layer has a melt index of 0.5-2 g / 10 min and a density of 0.91-0.92 g / cm 3 The linear low-density polyethylene used in the inner layer has a melt index of 1.5 to 2.5 g / 10 min and a density of 0.912 to 0.925 g / cm 3 ;

[0018] The processing aids used in the outer layer, middle layer and inner layer have a melt index of 1.5-2.5 g / 10 min and a density of 0.910-0.925 g / cm 3 .

[0019] The present invention also provides a method for preparing the high-buffering, anti-drop, and heat-insulating PE film described in the above scheme, comprising the following steps:

[0020] The raw materials for the outer layer, the middle layer and the inner layer are subjected to three-layer co-extrusion blown film to obtain the high-buffering, anti-drop and heat-insulating PE film; among the raw materials for the outer layer, the middle layer and the inner layer, the raw materials for at least one layer include foaming masterbatch.

[0021] The present invention also provides a composite film, which includes a thermal insulation layer, and the thermal insulation layer is the high-buffering, anti-drop, and thermal insulation PE film described in the above scheme or the high-buffering, anti-drop, and thermal insulation PE film prepared by the preparation method described in the above scheme.

[0022] Preferably, the composite film is a three-layer structure or a four-layer structure; the three-layer structure includes a printing layer, a barrier layer and a thermal insulation layer arranged in sequence; the four-layer structure includes a printing layer, a barrier layer, a thermal insulation layer and a PE heat sealing layer arranged in sequence; or, the four-layer structure includes a paper layer, a barrier layer, a printing layer and a thermal insulation layer arranged in sequence.

[0023] The present invention also provides a composite bag, which is prepared from the composite film described in the above scheme.

[0024] The present invention provides a high-buffered anti-drop heat-insulating PE film, which is made of a three-layer co-extruded blown film of an outer layer, a middle layer, and an inner layer; at least one of the outer layer, the middle layer, and the inner layer is a foaming structure. At least one of the outer layer, the middle layer, and the inner layer of the high-buffered anti-drop heat-insulating PE film provided by the present invention is a foaming structure, so that the PE film forms dense bubbles, which has the effect of blocking cold and hot air; prolonging the thawing time of some frozen drinks and the cooling time of hot drinks. Due to the good heat and cold insulation effect, it feels comfortable and does not feel cold or hot, and the appearance is more upscale, and the customer experience is better; and the foaming structure makes the PE film of the present invention have a buffering effect and is not easily damaged after falling. The results of the embodiment show that the high-buffered anti-drop heat-insulating PE film composite bag of the present invention is 3 to 4 hours longer than that of ordinary bags in thawing and cooling time, and 1kg of water is not broken after falling from a height of 1.5m, indicating that it has good buffering and anti-drop performance. In summary, the high-buffering, anti-drop, and thermal-insulating PE film provided by the present invention has the characteristics of excellent thermal insulation effect, light weight, softness, anti-drop, and good hand feel. It has a more upscale appearance and a good customer experience. It solves the timeliness problem of some products that require extended insulation and cooling time, and has broad market prospects.

[0025] Furthermore, the present invention also provides a specific formula for a three-layer structure of a high-buffering, drop-resistant and heat-insulating PE film. By strictly controlling the formula, the present invention can ensure that the PE film has high mechanical properties, tensile strength and elongation at break while obtaining dense bubbles. DETAILED DESCRIPTION

[0026] The invention provides a high-buffering, drop-resistant and heat-insulating PE film, which is made of a three-layer co-extruded blown film of an outer layer, a middle layer and an inner layer; at least one layer among the outer layer, the middle layer and the inner layer is a foaming structure.

[0027] In a specific embodiment of the present invention, the cells of the foaming structure are shuttle-shaped. Cells of this shape are not easy to be perforated and have good stability.

[0028] In the present invention, the raw materials for preparing at least one layer of the outer layer, middle layer and inner layer include foaming masterbatch; specifically, when only the raw materials for preparing the outer layer include foaming masterbatch, the mass of the foaming masterbatch is preferably 2-8% of the total mass of the raw materials for preparing the outer layer, preferably 3-5%; when only the raw materials for preparing the middle layer include foaming masterbatch, the mass of the foaming masterbatch is preferably 1.5-8% of the total mass of the raw materials for preparing the middle layer, preferably 3-6%; when only the raw materials for preparing the inner layer include foaming masterbatch, the mass of the foaming masterbatch is preferably 2-6% of the total mass of the raw materials for preparing the inner layer, preferably 4-5%; when any two layers of the outer layer, middle layer and inner layer contain foaming masterbatch, or all three layers contain foaming masterbatch, the mass of the foaming masterbatch in each layer is preferably 1-11% of the total mass of the raw materials for preparing the layer, preferably 3-8%.

[0029] In the present invention, the melt index of the foaming masterbatch is preferably 4 to 7 g / 10 min, more preferably 4.5 to 6 g / 10 min, and the density is preferably 0.913 to 0.955 g / cm 3 , more preferably 0.916 to 0.955 g / cm 3 Specifically, the model of the foaming masterbatch is preferably CFE-3361G and / or FM10PE; in a specific embodiment of the present invention, the foaming masterbatch model CFE-3361G is purchased from Guangzhou Benqi New Materials Co., Ltd., and its melt index is 6.0g / 10min and the density is 0.916g / cm 3 The foaming masterbatch model FM10PE was purchased from Foshan Jingxi New Material Technology Co., Ltd., with a melt index of 4.5g / 10min and a density of 0.955g / cm 3 The foaming masterbatch used in the present invention has the characteristics of uniform and fine pores and high closed cell rate.

[0030] In the present invention, the raw materials of the outer layer, middle layer and inner layer of the high-cushioning, anti-drop and thermal insulation PE film preferably also include polyethylene and processing aids, wherein the polyethylene used in the outer layer is preferably low-density polyethylene, linear low-density polyethylene and metallocene low-density polyethylene, and the polyethylene used in the inner layer is preferably low-density polyethylene, and the polyethylene used in the inner layer is preferably low-density polyethylene, linear low-density polyethylene and metallocene low-density polyethylene.

[0031] In the present invention, the raw materials for preparing the outer layer include, by weight: 10 to 60 parts of low-density polyethylene, 20 to 80 parts of linear low-density polyethylene, 15 to 60 parts of metallocene low-density polyethylene, 0 to 8 parts of foaming masterbatch, and 0.5 to 1.5 parts of processing aid;

[0032] The raw materials for preparing the middle layer include, by weight: 10 to 80 parts of low-density polyethylene, 0 to 8 parts of foaming masterbatch, and 0.5 to 1.5 parts of processing aid;

[0033] Calculated by weight, the raw materials for preparing the inner layer include: 15 to 50 parts of low-density polyethylene, 20 to 80 parts of metallocene low-density polyethylene, and 10 to 80 parts of linear low-density polyethylene; 0 to 8 parts of foaming masterbatch, and 0.5 to 1.5 parts of processing aid; among the raw materials for preparing the outer layer, middle layer, and inner layer, the weight percentages of the foaming masterbatch are not all 0.

[0034] In terms of mass fraction, the raw material for preparing the outer layer includes 10 to 60 parts of low-density polyethylene, preferably 20 to 50 parts; the melt index of the low-density polyethylene used in the outer layer is preferably 0.2 to 5 g / 10min, more preferably 0.3 to 4 g / 10min, and the density is preferably 0.920 to 0.935 g / cm 3 , more preferably 0.924 to 0.927 g / cm 3 The model of the low-density polyethylene used in the outer layer is preferably one or more of 951-000, PE3020D, 2420K and HP4024ZN, wherein the low-density polyethylene model 951-000 is purchased from Maoming Petrochemical, and its melt index is 2.0g / 10min and its density is 0.924g / cm 3 ; Low-density polyethylene of model PE3020D was purchased from Basel, with a melt index of 0.3 g / 10 min and a density of 0.927 g / cm 3 ; Low-density polyethylene of model 2420K was purchased from Daqing Petrochemical, with a melt index of 4.0g / 10min and a density of 0.924g / cm 3 ; Model HP4024ZN low-density polyethylene was purchased from Saudi Arabia Foundation, with a melt index of 4g / 10min and a density of 0.923g / cm 3In a specific embodiment of the present invention, when the outer layer adopts low-density polyethylene of model 951-000, its mass fraction is preferably 20-40 parts, more preferably 25-35 parts; when the outer layer adopts low-density polyethylene of model PE3020D, its mass fraction is preferably 10-50 parts, more preferably 20-40 parts; when the outer layer adopts low-density polyethylene of model 2420K, its mass fraction is preferably 15-60 parts, more preferably 25-45 parts; when the outer layer adopts low-density polyethylene of model HP4024ZN, its mass fraction is preferably 40-60 parts. The low-density polyethylene used in the outer layer of the present invention has the characteristics of few crystal points and good processability.

[0035] Based on the mass fraction of low-density polyethylene used in the outer layer, the raw material for preparing the outer layer includes 20 to 80 parts of linear low-density polyethylene, preferably 30 to 70 parts; the melt index of the linear low-density polyethylene used in the outer layer is preferably 0.3 to 3.5 g / 10min, more preferably 2 to 3 g / 10min, and the density is preferably 0.912 to 0.930 g / cm 3 , more preferably 0.918 to 0.925 g / cm 3 The linear low-density polyethylene used in the outer layer is preferably one or more of 7042, 1002YB and 2505H; wherein the linear low-density polyethylene of model 7042 is purchased from Maoming Petrochemical, and its melt index is 2.0g / 10min and density is 0.918g / cm 3 ; Linear low-density polyethylene of model 1002YB was purchased from ExxonMobil, with a melt index of 2.0 g / 10 min and a density of 0.918 g / cm 3 The linear low-density polyethylene of model 2505H was purchased from CNOOC Shell Petrochemical Co., Ltd., with a melt index of 0.5 g / 10 min and a density of 0.925 g / cm 3 In a specific embodiment of the present invention, when the outer layer adopts a linear low-density polyethylene of model 7042, its mass fraction is preferably 30 to 80 parts, more preferably 40 to 60 parts; when the outer layer adopts a linear low-density polyethylene of model 1002YB, its mass fraction is preferably 20 to 80 parts, more preferably 40 to 60 parts; when the outer layer adopts a linear low-density polyethylene of model 2505H, its mass fraction is preferably 25 to 80 parts, more preferably 40 to 60 parts. The linear low-density polyethylene used in the outer layer of the present invention has the properties of high composite strength and good processing.

[0036] Based on the mass fraction of low-density polyethylene used in the outer layer, the raw material for preparing the outer layer includes 15 to 60 parts of metallocene low-density polyethylene, preferably 20 to 50 parts. In the present invention, the melt index of the metallocene low-density polyethylene used in the outer layer is preferably 0.5 to 2.5 g / 10 min, more preferably 1 to 2 g / 10 min, and the density is preferably 0.908 to 0.930 g / cm 3 , more preferably 0.912 to 0.925 g / cm 3 In a specific embodiment of the present invention, the metallocene low-density polyethylene used in the outer layer is preferably one or more of 2012MA, 5400G and SP2520; wherein the metallocene low-density polyethylene of model 2012MA is purchased from ExxonMobil, and its melt index is 2.0g / 10min and its density is 0.912g / cm 3 ; Metallocene low-density polyethylene of model 5400G was purchased from Dow Chemical, with a melt index of 1.0 g / 10 min and a density of 0.916 g / cm 3 The metallocene low-density polyethylene of model SP2520 was purchased from Mitsui Chemicals, with a melt index of 2.0 g / 10 min and a density of 0.925 g / cm 3 In a specific embodiment of the present invention, when the outer layer adopts the metallocene low-density polyethylene of model 2012MA, its mass fraction is preferably 15 to 30 parts, more preferably 20 to 25 parts; when the outer layer adopts the metallocene low-density polyethylene of model 5400G, its mass fraction is preferably 20 to 50 parts, more preferably 30 to 40 parts; when the outer layer adopts the metallocene low-density polyethylene of model SP2520, its mass fraction is preferably 20 to 60 parts, more preferably 30 to 50 parts. The metallocene low-density polyethylene used in the outer layer of the present invention has the properties of high composite fastness and good transparency.

[0037] Based on the mass fraction of low-density polyethylene used in the outer layer, the raw materials for preparing the outer layer include 0 to 8 parts of foaming masterbatch. The melt index, model and purchase manufacturer of the foaming masterbatch are not repeated; in a specific embodiment of the present invention, the raw materials for preparing the outer layer may include foaming masterbatch or may not include foaming masterbatch. Specifically, when the outer layer includes foaming masterbatch, the mass fraction of the foaming masterbatch is preferably 1 to 8 parts, more specifically, when the foaming masterbatch model CFE-3361G is used, its mass fraction is preferably 1 to 2.5 parts, more preferably 1.5 to 2 parts, and when the foaming masterbatch model FM10PE is used, its mass fraction is preferably 5 to 8 parts, more preferably 6 to 7 parts.

[0038] Based on the mass fraction of low-density polyethylene used in the outer layer, the raw material for preparing the outer layer includes 0.5 to 1.5 parts of processing aid, preferably 0.8 to 1.2 parts; the melt index of the processing aid used in the outer layer is preferably 1.5 to 2.5 g / 10 min, more preferably 2 to 2.1 g / 10 min, and the density is preferably 0.910 to 0.925 g / cm 3 , more preferably 0.915 to 0.920 g / cm 3 The processing aid is preferably a functional masterbatch prepared from a fluoropolymer and a polyolefin resin; the processing aid is preferably PA0895LD and / or PEA-3S. In a specific embodiment of the present invention, the processing aid model PA0895LD is purchased from Suzhou Constant Engineering Plastics Co., Ltd., and its melt index is 2.1 g / min and the density is 0.915 g / cm 3 The processing aid model PEA-3S was purchased from Huayi Technology Co., Ltd., with a melt index of 2.1 g / min and a density of 0.920 g / cm 3 In a specific embodiment of the present invention, when the outer layer adopts a processing aid of model PA0895LD, its mass fraction is preferably 0.5 to 1 part, more preferably 0.6 to 0.8 parts, and when the outer layer adopts a processing aid of model PEA-3S, its mass fraction is preferably 0.5 to 1.5 parts, more preferably 0.6 to 1.2 parts. The processing aid used in the present invention can effectively reduce die buildup, reduce crystal point, reduce extrusion pressure and improve production efficiency.

[0039] In terms of mass fraction, the raw material for preparing the middle layer includes 10 to 98 parts of low-density polyethylene, preferably 20 to 80 parts. In the present invention, the melt index of the low-density polyethylene used in the middle layer is preferably 0.1 to 3.5 g / 10 min, more preferably 0.25 to 3 g / 10 min, and the density is preferably 0.920 to 0.940 g / cm 3 , more preferably 0.924 to 0.933 g / cm 3 The low-density polyethylene used in the middle layer is preferably one or more of 2420D, 2420F and 151BW, and more preferably any two of them are used in combination; wherein the low-density polyethylene of model 2420D is purchased from CNOOC Shell, and its melt index is 0.25g / 10min and density is 0.924g / cm 3 ; Low-density polyethylene of model 2420F was purchased from CNOOC Shell, with a melt index of 0.75 g / 10 min and a density of 0.924 g / cm 3 ; Low-density polyethylene of model 151BW was purchased from ExxonMobil, with a melt index of 3 g / 10 min and a density of 0.933 g / cm 3; In a specific embodiment of the present invention, when the middle layer adopts low-density polyethylene with model number 2420D, its mass fraction is preferably 10-40 parts, and more preferably 20-30 parts; when the middle layer adopts low-density polyethylene with model number 2420F, its mass fraction is preferably 30-80 parts, and more preferably 50-70 parts; when the middle layer adopts low-density polyethylene with model number 151BW, its mass fraction is preferably 15-50 parts, and more preferably 20-40 parts; The low-density polyethylene used in the middle layer of the present invention has the characteristics of few crystal points, can form uniform and dense bubbles by reacting with a foaming agent, and has good processability.

[0040] Based on the mass fraction of low-density polyethylene used in the middle layer, the raw materials for preparing the middle layer include 0 to 8 parts of foaming masterbatch; the melt index, model and purchasing manufacturer of the foaming masterbatch are not repeated here; in a specific embodiment of the present invention, the raw materials for preparing the middle layer may include foaming masterbatch or may not include foaming masterbatch. Specifically, when the middle layer includes foaming masterbatch, the mass fraction of the foaming masterbatch is preferably 1 to 8 parts, more specifically, when the foaming masterbatch model CFE-3361G is used, its mass fraction is preferably 1 to 2.5 parts, more preferably 1.5 to 2 parts, and when the foaming masterbatch model FM10PE is used, its mass fraction is preferably 5 to 8 parts, more preferably 6 to 7 parts.

[0041] Based on the mass fraction of low-density polyethylene used in the middle layer, the raw materials for preparing the middle layer include 0.5 to 1.5 parts of processing aids, preferably 0.8 to 1.2 parts; the melt index, model and purchasing manufacturer of the processing aid used in the middle layer are preferably consistent with the processing aid used in the outer layer, and are not repeated here; in a specific embodiment of the present invention, when the middle layer uses a processing aid with model PA0895LD, its mass fraction is preferably 0.5 to 1 part, more preferably 0.6 to 0.8 parts, and when the middle layer uses a processing aid with model PEA-3S, its mass fraction is preferably 0.5 to 1.5 parts, more preferably 0.6 to 1.2 parts.

[0042] In terms of mass fraction, the raw material for preparing the inner layer includes 15 to 50 parts of low-density polyethylene, preferably 20 to 40 parts; the melt index of the low-density polyethylene used in the inner layer is preferably 0.3 to 3.5 g / 10 min, more preferably 0.8 to 2.5 g / 10 min, and the density is preferably 0.920 to 0.930 g / cm 3 , more preferably 0.923 to 0.924 g / cm 3 The model of the low-density polyethylene used in the inner layer is preferably one or more of 2420H, Q281 and HP0823J; specifically, the low-density polyethylene model 2420H is purchased from CNOOC Shell, and its melt index is 2.0g / 10min and its density is 0.924g / cm3 The low-density polyethylene model Q281 was purchased from Shanghai Petrochemical, with a melt index of 2.8g / 10min and a density of 0.924g / cm 3 The low-density polyethylene model HP0823J was purchased from Saudi Arabia, with a melt index of 0.8g / 10min and a density of 0.923g / cm 3 In a specific embodiment of the present invention, when the inner layer adopts low-density polyethylene of model 2426H, its mass fraction is preferably 15 to 40 parts, more preferably 20 to 35 parts; when the inner layer adopts low-density polyethylene of model Q281, its mass fraction is preferably 20 to 40 parts, preferably 25 to 35 parts; when the inner layer adopts low-density polyethylene of model HP0823J, its mass fraction is preferably 25 to 50 parts, more preferably 30 to 45 parts. The low-density polyethylene used in the inner layer of the present invention has the characteristics of good opening and good processing.

[0043] Based on the mass fraction of the low-density polyethylene used in the inner layer, the raw material for preparing the inner layer includes 20 to 80 parts of metallocene low-density polyethylene, preferably 30 to 60 parts; the melt index of the metallocene low-density polyethylene used in the inner layer is preferably 0.5 to 2 g / 10min, preferably 0.8 to 1.5 g / 10min, and the density is preferably 0.91 to 0.92 g / cm 3 , more preferably 0.914 to 0.918 g / cm 3 The metallocene low-density polyethylene used in the inner layer is preferably XP8784MK, FK1826 or 1018BM; Specifically, the low-density polyethylene of model XP8784MK was purchased from ExxonMobil, and its melt index is 0.8g / 10min and the density is 0.914g / cm 3 ; Low-density polyethylene of model FK1826 was purchased from Borouge, with a melt index of 1.5 g / 10 min and a density of 0.918 g / cm 3 ; Low-density polyethylene of model 1018BM was purchased from LG Chemical, with a melt index of 1.0 g / 10 min and a density of 0.918 g / cm 3 In a specific embodiment of the present invention, when the inner layer adopts the metallocene low-density polyethylene of model XP8784MK, its mass fraction is 25-50 parts, preferably 30-40 parts; when the inner layer adopts the metallocene low-density polyethylene of model FK1826, its mass fraction is 20-80 parts, preferably 30-50 parts; when the inner layer adopts the metallocene low-density polyethylene of model 1018BM, its mass fraction is 30-70 parts, preferably 40-50 parts. The metallocene low-density polyethylene used in the inner layer of the present invention has the properties of high strength, good toughness, low sealing temperature and high heat sealing strength.

[0044] Based on the mass fraction of the low-density polyethylene used in the inner layer, the raw material for preparing the inner layer includes 10 to 80 parts of linear low-density polyethylene, more preferably 10 to 40 parts or 30 to 80 parts; the melt index of the linear low-density polyethylene used in the inner layer is preferably 1.5 to 2.5 g / 10min, more preferably 1.8 to 2 g / 10min, and the density is preferably 0.912 to 0.925 g / cm 3 , more preferably 0.918 to 0.920 g / cm 3 The linear low-density polyethylene used in the inner layer is preferably one or more of 7042, 1002BU and 218WJ; wherein the linear low-density polyethylene of model 7042 is purchased from Maoming Petrochemical, and its melt index is 2.0g / 10min and density is 0.918g / cm 3 The linear low-density polyethylene model 1002BU was purchased from ExxonMobil, with a melt index of 2.0 g / 10 min and a density of 0.918 g / cm 3 The linear low-density polyethylene model 218WJ was purchased from Saudi Arabia, with a melt index of 2.0g / 10min and a density of 0.918g / cm 3 In a specific embodiment of the present invention, when a linear low-density polyethylene of model 7042 is used, its mass fraction is preferably 30 to 80 parts, more preferably 40 to 60 parts; when a linear low-density polyethylene of model 1002BU or 218WJ is used, its mass fraction is preferably 10 to 40 parts, more preferably 20 to 30 parts. The low-density polyethylene used in the inner layer of the present invention has the properties of good opening smoothness and good strength.

[0045] Based on the mass fraction of low-density polyethylene used in the inner layer, the raw materials for preparing the inner layer include 0 to 8 parts of foaming masterbatch; in a specific embodiment of the present invention, the raw materials for preparing the middle layer may include foaming masterbatch or may not include foaming masterbatch. Specifically, when the middle layer includes foaming masterbatch, the mass fraction of the foaming masterbatch is preferably 1 to 8 parts. More specifically, when the foaming masterbatch model CFE-3361G is used, its mass fraction is preferably 1 to 2.5 parts, more preferably 1.5 to 2 parts. When the foaming masterbatch model FM10PE is used, its mass fraction is preferably 5 to 8 parts, more preferably 6 to 7 parts.

[0046] Based on the mass fraction of low-density polyethylene used in the inner layer, the raw materials for preparing the inner layer include 0.5 to 1.5 parts of processing aids, preferably 0.8 to 1.2 parts; the melt index, model and purchasing manufacturer of the processing aid used in the middle layer are preferably consistent with the processing aid used in the outer layer, and are not repeated here; in a specific embodiment of the present invention, when the inner layer adopts a processing aid with model PA0895LD, its mass fraction is preferably 0.5 to 1 part, more preferably 0.6 to 0.8 parts, and when the inner layer adopts a processing aid with model PEA-3S, its mass fraction is preferably 0.5 to 1.5 parts, more preferably 0.6 to 1.2 parts.

[0047] In the present invention, taking the total mass of the outer layer, the middle layer and the inner layer as 100%, the mass fraction of the outer layer is preferably 15-30%, the mass fraction of the middle layer is preferably 40-70%, and the mass fraction of the inner layer is preferably 15-30%; the thickness of the high-buffering, anti-drop and thermal insulation PE film is preferably 100-200 μm, more preferably 150 μm; the thickness ratio of the outer layer, the middle layer and the inner layer is preferably 1-3:2-4:1-3, more preferably 3:4:3, 1:2:1, 1:3:1 or 1:4:1.

[0048] In the present invention, the longitudinal tensile strength of the high buffer anti-drop insulation PE film is preferably 23-24.5 MPa, more preferably 23.7-24.1 MPa, the transverse tensile strength is preferably 21-23 MPa, more preferably 21.5-22.5 MPa, the longitudinal elongation at break is preferably 415-435%, more preferably 420-425%, the transverse elongation at break is preferably 615-640%, more preferably 620-630%, and the density is preferably 0.5-0.6 g / cm 3 , more preferably 0.565 to 0.59 g / cm 3 .

[0049] The present invention also provides a method for preparing the high-buffering, anti-drop, and heat-insulating PE film described in the above scheme, comprising the following steps:

[0050] The raw materials for the outer layer, the middle layer and the inner layer are subjected to three-layer co-extrusion blown film to obtain the high-buffering, anti-drop and heat-insulating PE film; among the raw materials for the outer layer, the middle layer and the inner layer, the raw materials for at least one layer include foaming masterbatch.

[0051] In the present invention, the process of three-layer co-extrusion blown film specifically includes: the raw materials for the outer layer, the middle layer and the inner layer are mixed in proportion by an automatic batching system and then respectively sent to the outer layer, the middle layer and the inner layer extruders for melting and plasticization, the obtained glue liquid is transported to the die head, and the film is extruded and blown to obtain a film bubble. After the film bubble is cooled by air, it is successively passed through a stabilizing ring and a herringbone arrangement to an upper traction rotation, the cylinder is flattened and then enters a corona treatment device through a guide roller for corona treatment, and then trimmed, pulled down and rolled up to obtain the high-buffering, drop-resistant and heat-insulating PE film.

[0052] In the present invention, the outer layer extruder, the middle layer extruder and the inner layer extruder are all provided with 5 heating zones, which are recorded as zones 1 to 5 in the order in which the raw materials pass; the temperature of zone 1 of the outer layer extruder is preferably 170±5°C, the temperature of zone 2 is preferably 175±5°C, the temperature of zone 3 is preferably 170±5°C, the temperature of zone 4 is preferably 165±5°C, and the temperature of zone 5 is preferably 160±5°C; the temperature of zone 1 of the middle layer extruder is preferably 165±5°C, the temperature of zone 2 is preferably 170±5°C, the temperature of zone 3 is preferably 165±5°C, the temperature of zone 4 is preferably 162±5°C, and the temperature of zone 5 is preferably 160±5°C; the temperature of zone 1 of the inner layer extruder is preferably 175±5°C, the temperature of zone 2 is preferably 178±5°C, the temperature of zone 3 is preferably 172±5°C, the temperature of zone 4 is preferably 170±5°C, and the temperature of zone 5 is preferably 165±5°C.

[0053] In the present invention, the pressure of the outer layer extruder is preferably 220-285 bar, more preferably 245 bar, the pressure of the middle layer extruder is preferably 280-360 bar, more preferably 320 bar, and the pressure of the inner layer extruder is preferably 245-320 bar, more preferably 295 bar.

[0054] In the present invention, the die is divided into four heating zones, which are respectively recorded as zones 1 to 4 in the order in which the glue passes through. The temperature of zone 1 of the die is preferably 180±5°C, the temperature of zone 2 is preferably 185±5°C, the temperature of zone 3 is preferably 188±5°C, and the temperature of zone 4 is preferably 182±5°C.

[0055] The present invention also provides a composite film (referred to as a high-buffering, anti-drop, and thermal-insulating composite film), which includes a thermal insulation layer, and the thermal insulation layer is the high-buffering, anti-drop, and thermal-insulating PE film described in the above scheme or the high-buffering, anti-drop, and thermal-insulating PE film prepared by the preparation method described in the above scheme.

[0056] In the present invention, the composite film is preferably a three-layer structure or a four-layer structure; the three-layer structure preferably includes a printing layer, a barrier layer and a thermal insulation layer arranged in sequence; the printing layer is preferably a polyester film (PET), and the thickness of the polyester film is preferably 12-15 μm; the barrier layer is preferably an aluminum foil or a polyester aluminized film (VMPET), the thickness of the aluminum foil is preferably 7-25 μm, and the thickness of the VMPET is preferably 12 μm; when the barrier layer is an aluminum foil, the thickness ratio of the printing layer, the barrier layer and the thermal insulation layer is preferably 12-15:7-25:100-200, and when the barrier layer is VMPET, the thickness ratio of the printing layer, the barrier layer and the thermal insulation layer is preferably 12-15:12:100-200.

[0057] In the present invention, the four-layer structure preferably includes a printing layer, a barrier layer, a heat-insulating layer and a PE heat-sealing layer arranged in sequence; the printing layer, the barrier layer and the heat-insulating layer are all consistent with those in the three-layer structure and are not described in detail herein; the present invention has no special requirements for the PE heat-sealing layer, and the ones familiar to those skilled in the art can be adopted, and the thickness of the PE heat-sealing layer is preferably 40 to 60 μm; when the barrier layer is aluminum foil, the thickness ratio of the printing layer, the barrier layer, the heat-insulating layer and the PE heat-sealing layer is preferably 12 to 15:7 to 25:100 to 150:40 to 60; when the barrier layer is VMPET, the thickness ratio of the printing layer, the barrier layer, the heat-insulating layer and the PE heat-sealing layer is preferably 12 to 15:12:100 to 150:40 to 60.

[0058] Or, the four-layer structure includes a paper layer, a barrier layer, a printing layer and a heat-insulating layer arranged in sequence, wherein the type of the barrier layer is consistent with that in the three-layer structure and is not repeated here; the paper layer is preferably kraft paper for printing, and the thickness of the paper layer is preferably 60-80 μm; the printing layer is preferably a PET layer or a nylon layer. The present invention uses PET or nylon as the printing layer, and the material has good heat resistance, is easy to print, and is easy to make bags; the thickness of the PET layer is preferably 12 μm, and the thickness of the nylon layer is preferably 15 μm; the present invention has no special requirements for the PET layer or the nylon layer, and those familiar to those skilled in the art can be used.

[0059] In the present invention, the method for preparing the three-layer composite film preferably comprises the following steps:

[0060] Compounding the printing layer and the barrier layer by means of an adhesive to obtain a printing layer / barrier layer composite film;

[0061] The printed layer / barrier layer composite film and the high-buffering anti-drop thermal insulation PE film are composited with a solvent-free adhesive to obtain the composite film with the three-layer structure.

[0062] In the present invention, the printing layer is preferably printed according to demand before lamination. The present invention has no special requirements for the printing method, and the gravure printing process well known to those skilled in the art can be used; the amount of adhesive used when the printing layer and the barrier layer are laminated is preferably 3.0 to 3.8 g / m 2 ; The printing layer and the barrier layer are preferably laminated by dry lamination. The present invention has no special requirements on the specific operating conditions of the dry lamination. The dry lamination process well known to those skilled in the art can be adopted. In a specific embodiment of the present invention, the glue solution is coated on the printing layer, and then the barrier layer is laminated; In the present invention, the adhesive used for laminating the printing layer and the barrier layer is preferably TAKELACTM PP-3111 / TAKENATETM I-3000 dry lamination adhesive of Tianjin Tianhuan Polyurethane Co., Ltd. When the dry lamination adhesive is used, PP-3111, I-3000 and ethyl acetate are preferably mixed, and the mass ratio of PP-3111, I-3000 and ethyl acetate is preferably 8:1:10.8; After lamination, it is preferably cured, and the curing temperature is preferably 50°C±5°C, and the curing time is preferably 72 hours.

[0063] In the present invention, the solvent-free adhesive is preferably a two-component solvent-free polyurethane composite adhesive I-2450A / PP-2450FX of Tianjin Tianhuan Polyurethane Co., Ltd., with a solid content of 100%; the process conditions for compounding the printed layer / barrier layer composite film and the high buffer anti-drop insulation PE film include: the mixing temperature is preferably 50°C, specifically, the temperature of I-2450A and PP-2450FX are both set to 50°C, and then mixing is performed; the coating temperature is preferably 50°C, specifically, the steel rollers of the coating and gluing system are set to 50°C; the glue ratio: the mass ratio of I-2450A and PP-2450FX is preferably 100:50; the glue amount is preferably 1.6-2.2g / m 2 , more preferably 1.6 to 2.0 g / m 2 After compounding, it is preferably ripened, the ripening temperature is preferably 45°C ± 5°C, the ripening time is preferably 48h, and after ripening, it is preferably taken out and placed at room temperature for 12 hours before subsequent cutting and bagging.

[0064] In the present invention, when the composite film is a four-layer structure, and the four-layer structure includes a printing layer, a barrier layer, a heat insulation layer and a PE heat sealing layer arranged in sequence, the preparation method of the composite film preferably includes the following steps:

[0065] Compounding the printing layer and the barrier layer by means of an adhesive to obtain a printing layer / barrier layer composite film;

[0066] Compounding the printed layer / barrier layer composite film and the high-buffering anti-drop thermal insulation PE film by using a solvent-free adhesive to obtain a printed layer / barrier layer / thermal insulation layer composite film;

[0067] The printed layer / barrier layer / heat-insulating layer composite film is composited with the PE heat-sealing layer by using a solvent-free adhesive to obtain a composite film with a four-layer structure.

[0068] In the present invention, the method of compounding the printing layer and the barrier layer, and the method of compounding the printing layer / barrier layer composite film and the high buffering, anti-drop and thermal insulation PE film are consistent with the preparation process of the three-layer structure composite film, and will not be repeated here; the printing layer / barrier layer / thermal insulation layer composite film is compounded with the PE heat sealing layer by a solvent-free adhesive, and the specific compounding conditions are consistent with the conditions for compounding the printing layer / barrier layer composite film and the high buffering, anti-drop and thermal insulation PE film by a solvent-free adhesive during the preparation process of the three-layer structure composite film, and will not be repeated here.

[0069] In the present invention, when the composite film is a four-layer structure, and the four-layer structure includes a paper layer, a barrier layer, a printing layer and a heat insulation layer arranged in sequence, the method for preparing the composite film preferably includes the following steps:

[0070] Compounding the paper layer and the barrier layer by means of an adhesive to obtain a paper layer / barrier layer composite film;

[0071] Compounding the paper layer / barrier layer composite film with an adhesive and a printing layer to obtain a paper layer / barrier layer / printing layer composite film;

[0072] The paper layer / barrier layer / printing layer composite film is composited with the high buffering anti-drop heat insulation PE film by using a solvent-free adhesive to obtain a composite film with a four-layer structure.

[0073] In the present invention, the paper layer is preferably printed before lamination, and the printing method is preferably gravure printing; the paper layer and the barrier layer are preferably compounded by a solvent-free compounding process, and the adhesive used is preferably a solvent-free single-component adhesive. In a specific embodiment of the present invention, the solvent-free single-component adhesive is preferably Wanhua Chemical's solvent-free single-component adhesive 6091; the adhesive amount of the paper layer and the barrier layer when compounding is preferably 3.5-5.5 g / m 2 After compounding, it is preferably ripened, the ripening temperature is preferably 55°C ± 5°C, and the ripening time is preferably 48h.

[0074] In the present invention, when the paper layer / barrier layer composite film is composited with the printing layer, the method adopted is preferably dry composite, and the amount of adhesive used is preferably 3.0-4 g / m 2The adhesive used for the dry composite is preferably TAKELACTM PP-3111 / TAKENATETM I-3000 dry composite glue produced by Tianjin Tianhuan Polyurethane Co., Ltd. When the dry composite glue is used, PP-3111, I-3000 and ethyl acetate are preferably mixed, and the mass ratio of PP-3111, I-3000 and ethyl acetate is preferably 8:1:10.8; after composite, it is preferably ripened, and the ripening temperature is preferably 50°C±5°C, and the ripening time is preferably 72 hours.

[0075] In the present invention, the amount of solvent-free adhesive used for the composite film of the paper layer / barrier layer / printing layer and the high buffer anti-drop insulation PE film is preferably 1.6 to 2.2 g / m 2 The type of solvent-free adhesive and the compounding conditions are consistent with those in the preparation process of the three-layer composite film, and will not be repeated here.

[0076] The present invention also provides a composite bag, which is prepared from the composite film of the above scheme. The present invention has no special requirements on the bag shape of the composite bag, and any bag shape well known to those skilled in the art can be used.

[0077] The present invention has no special requirements for the preparation method of the composite bag. The composite film can be cut and bagged by a method well known to those skilled in the art. In a specific embodiment of the present invention, the operating conditions for bag making preferably include: the transverse sealing temperature is preferably 175°C to 195°C, the transverse sealing heat sealing pressure is preferably 4 to 6 kg, the heat sealing time is preferably 0.5 to 1 second, and the sealing line width is preferably 10±1.5 mm; the longitudinal sealing temperature is preferably 170°C to 190°C, the longitudinal sealing heat sealing pressure is preferably 4 to 6 kg, the heat sealing time is preferably 0.5 to 1 second, and the sealing line width is preferably 10±1.5 mm; the nozzle temperature is preferably 180 to 200°C, the nozzle heat sealing pressure is preferably 4.5 to 6.5 kg, and the heat sealing time is preferably 0.5 to 1 second.

[0078] The composite bag provided by the present invention has good heat insulation and cold insulation properties, and can extend the thawing time of frozen drinks and the cooling time of hot drinks; and it feels comfortable, without feeling cold or hot, and the customer experience is good; in a specific embodiment of the present invention, the composite bag provided by the present invention can be used for packaging foods that have a better flavor after refrigeration, such as fruit juice, fruit puree, jelly, tortoise jelly, wine, milk, water, special beverages, special liquid foods, etc.; or for packaging foods that have a better flavor after heating, such as coffee, fruit juice, fruit puree, wine, milk, water, special beverages, special liquid foods, etc.; or for other soft packaging that requires heat insulation, such as health products or medicines.

[0079] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0080] The properties and manufacturers of the raw materials used in the examples of the present invention are shown in Table 1.

[0081] Table 1 Raw material properties and purchasing manufacturers

[0082]

[0083] Example 1

[0084] 1. Preparation of high buffer anti-drop thermal insulation PE film

[0085] The high-buffering, drop-resistant and heat-insulating PE film of this embodiment is made of a three-layer co-extruded blown film of an outer layer, a middle layer and an inner layer. The weight percentages of the materials of each layer between the three layers are: 30% for the outer layer, 40% for the middle layer, and 30% for the inner layer.

[0086] The amount of raw materials for each layer is shown in Table 2. The total thickness of the high-buffered anti-drop thermal insulation PE film is 150 μm. The preparation method is as follows:

[0087] The raw materials of the outer layer, middle layer and inner layer are mixed in proportion by an automatic batching system and sent to the outer layer, middle layer and inner layer extruders. The raw materials of the outer layer, middle layer and inner layer are melted and plasticized and then sent to the die head for extrusion and film blowing. Then, the film is cooled by air cooling, and then the film is flattened by the upper traction rotation through a stabilizing ring and a herringbone arrangement, and then sent to the corona treatment device through a guide roller for corona treatment. Then, the trimmed edge is sent to the front and rear winding device through the lower traction roller for front and rear winding, and a 150μm high-buffering, anti-drop and heat-insulating PE film is obtained.

[0088] The temperatures and pressures of the outer, middle and inner layer extruders and die heads are shown in Table 3.

[0089] Table 2 Raw material ratios of Examples 1 to 8 and Comparative Examples 2 to 4

[0090]

[0091]

[0092] Table 3 Temperature and pressure of extruder and die head

[0093] temperature Zone 1 / ℃ Zone 2 / ℃ Zone 3 / ℃ Zone 4 / ℃ Zone 5 / ℃ Pressure(bar) Outer Layer 170 175 170 165 160 245 Middle level 165 170 165 162 160 320 Inner Layer 175 178 172 170 165 295 Die head 180 185 188 182 / /

[0094] 2. Preparation of three-layer structure high buffer anti-drop heat insulation composite film and bag

[0095] The composite film is a three-layer structure, which is composed of a printing layer, a barrier layer and a heat-insulating layer arranged in sequence, wherein the printing layer is a polyester (PET) film, and a 12μm printing film is purchased from DuPont Hongji; the barrier layer is an Al foil, and a 7μm aluminum foil for packaging is purchased from Shanghai Shenhuo Aluminum Foil Co., Ltd. The heat-insulating layer is a high-buffering anti-drop heat-insulating PE film layer with a thickness of 150μm prepared in the above steps. The three-layer composite film is represented by PET12 / AL7 / heat-insulating PE film 150.

[0096] The preparation method of the high-buffering anti-drop heat-insulating composite film and bag is as follows:

[0097] (1) The printed layer polyester film is printed using the gravure process according to customer requirements.

[0098] (2) The printed polyester film and aluminum foil are laminated by dry lamination process. The glue is TAKELACTM PP-3111 / TAKENATETM I-3000 dry lamination glue of Tianjin Tianhuan Polyurethane Co., Ltd. When using, PP-3111, I-3000 and ethyl acetate are mixed. The mass ratio of PP-3111, I-3000 and ethyl acetate is 8:1:10.8; the glue amount is 3.5g / m 2 After compounding, place it in a curing room at 50℃±5℃ for 72h.

[0099] (3) The cured PET / AL two-layer composite film is compounded with the high-buffered anti-drop insulation PE film using solvent-free glue. The glue is the two-component solvent-free polyurethane composite adhesive I-2450A / PP-2450FX of Tianjin Tianhuan Polyurethane Co., Ltd., with a solid content of 100%. The process conditions used for compounding are as follows: mixing temperature: both components A and B are set to 50°C; coating temperature: the steel rollers of the coating and gluing system are set to 50°C; glue ratio I-2450A / PP-2450FX = 100 / 50 (mass ratio); ④, the glue amount is 2g / m 2 After compounding, put it into a curing room at 45℃±5℃ for 48h. After taking it out, leave it at room temperature for 12h before cutting and bagging.

[0100] (4) Cut the cured three-layer composite film into bags; the bag making process is as follows

[0101] Horizontal sealing temperature: 175℃~195℃, heat sealing pressure 4.8kg, time 0.8 seconds, sealing line width 10±1.5mm;

[0102] Longitudinal sealing temperature: 170℃~190℃, heat sealing pressure 5.2kg, time 0.8s, sealing line width 10±1.5mm;

[0103] Nozzle temperature: 185°C, heat sealing pressure 5.5kg, time 1.0 second.

[0104] 3. Preparation of four-layer high-buffer, anti-drop, heat-insulating composite films and bags

[0105] The composite film has a four-layer structure, consisting of a paper layer, an aluminum foil, a nylon layer and an insulation layer arranged in sequence, wherein the insulation layer is a high-buffering, anti-drop and heat-insulating PE film layer with a thickness of 150 μm prepared in the above steps; wherein the paper is a composite paper purchased from Anhui Desen Special Paper Co., Ltd., the aluminum foil is a 7 μm aluminum foil for packaging purchased from Shanghai Shenhuo Aluminum Foil Co., Ltd., and the nylon is a 15-micron thick nylon purchased from Xiamen Changsu.

[0106] The preparation method of the high-buffering anti-drop heat-insulating composite film and bag is as follows:

[0107] (1) The printed paper and aluminum foil are laminated using a solvent-free lamination process. The glue used is Wanhua Chemical's solvent-free single-component glue 6091, and the glue amount is 5g / m 2 After compounding, place it in a curing room at 55℃±5℃ for 48h.

[0108] (2) The paper / AL composite film and nylon are dry-compounded, and the glue is TAKELACTM PP-3111 / TAKENATETM I-3000 dry composite glue from Tianjin Tianhuan Polyurethane Co., Ltd. When using, PP-3111, I-3000 and ethyl acetate are mixed, wherein the weight ratio of PP-3111, I-3000 and ethyl acetate is 8:1:10.8; the glue amount is 3.5g / m 2 After compounding, place it in a curing room at 50℃±5℃ for 72h.

[0109] (3) The three-layer composite film of the cured paper / AL / NY was composited with the high-buffering anti-drop insulation PE film using solvent-free glue. The glue used was the two-component solvent-free polyurethane composite adhesive I-2450A / PP-2450FX of Tianjin Tianhuan Polyurethane Co., Ltd., with a solid content of 100%. The composite process conditions were as follows: mixing temperature: both components A and B were set to 50°C; coating temperature: the steel rollers of the coating and gluing system were set to 50°C; glue ratio I-2450A / PP-2450FX = 100 / 50 (mass ratio); the glue amount was 1.8 g / m 2 After compounding, put it into a curing room at 45℃±5℃ for 48h. After taking it out, leave it at room temperature for 12h before cutting and bagging.

[0110] (4) Cut the cured 4-layer composite film into bags; the bag making process is as follows

[0111] Horizontal sealing temperature: 175℃~195℃, heat sealing pressure 5.0kg, time 1 second, sealing line width 10±1.5mm;

[0112] Longitudinal sealing temperature: 170℃~190℃, heat sealing pressure 5.8kg, time 1 second, sealing line width 10±1.5mm;

[0113] Nozzle temperature: 192°C, heat sealing pressure 6.0kg, time 1.0 second.

[0114] Example 2

[0115] The amount of raw materials used in each layer is shown in Table 2. The weight percentages of the materials in each layer between the three layers are: 25% for the outer layer, 50% for the middle layer, and 25% for the inner layer; the total thickness of the high-buffering, anti-drop, and heat-insulating PE film is 150 μm, and the preparation method is the same as that in Example 1.

[0116] The preparation methods of the three-layer high-buffering, anti-drop, and heat-insulating composite film and bag, and the four-layer high-buffering, anti-drop, and heat-insulating composite film and bag are the same as those in Example 1.

[0117] Example 3

[0118] The amount of raw materials used in each layer is shown in Table 2. The weight percentages of the materials in each layer between the three layers are: 20% for the outer layer, 55% for the middle layer, and 25% for the inner layer; the total thickness of the high-buffering, anti-drop, and heat-insulating PE film is 150 μm, and the preparation method is the same as that in Example 1.

[0119] The preparation methods of the three-layer high-buffering, anti-drop, and heat-insulating composite film and bag, and the four-layer high-buffering, anti-drop, and heat-insulating composite film and bag are the same as those in Example 1.

[0120] Example 4

[0121] The amount of raw materials used in each layer is shown in Table 2. The weight percentages of the materials in each layer between the three layers are: 20% for the outer layer, 60% for the middle layer, and 20% for the inner layer; the total thickness of the high-buffering, anti-drop, and heat-insulating PE film is 150 μm, and the preparation method is the same as that in Example 1.

[0122] The preparation methods of the three-layer high-buffering, anti-drop, and heat-insulating composite film and bag, and the four-layer high-buffering, anti-drop, and heat-insulating composite film and bag are the same as those in Example 1.

[0123] Example 5

[0124] The amount of raw materials used in each layer is shown in Table 2. The weight percentages of the materials in each layer between the three layers are: 20% for the outer layer, 50% for the middle layer, and 30% for the inner layer; the total thickness of the high-buffering, anti-drop, and heat-insulating PE film is 150 μm, and the preparation method is the same as that in Example 1.

[0125] The preparation methods of the three-layer high-buffering, anti-drop, and heat-insulating composite film and bag, and the four-layer high-buffering, anti-drop, and heat-insulating composite film and bag are the same as those in Example 1.

[0126] Example 6

[0127] The amount of raw materials used in each layer is shown in Table 2. The weight percentages of the materials in each layer between the three layers are: 30% for the outer layer, 40% for the middle layer, and 30% for the inner layer; the total thickness of the high-buffering, anti-drop, and heat-insulating PE film is 150 μm, and the preparation method is the same as that in Example 1.

[0128] The preparation methods of the three-layer high-buffering, anti-drop, and heat-insulating composite film and bag, and the four-layer high-buffering, anti-drop, and heat-insulating composite film and bag are the same as those in Example 1.

[0129] Example 7

[0130] The amount of raw materials used in each layer is shown in Table 2. The weight percentages of the materials in each layer between the three layers are: 25% for the outer layer, 50% for the middle layer, and 25% for the inner layer; the total thickness of the high-buffering, anti-drop, and heat-insulating PE film is 150 μm, and the preparation method is the same as that in Example 1.

[0131] The preparation methods of the three-layer high-buffering, anti-drop, and heat-insulating composite film and bag, and the four-layer high-buffering, anti-drop, and heat-insulating composite film and bag are the same as those in Example 1.

[0132] Example 8

[0133] The amount of raw materials used in each layer is shown in Table 2. The weight percentages of the materials in each layer between the three layers are: 25% for the outer layer, 45% for the middle layer, and 30% for the inner layer; the total thickness of the high-buffering, anti-drop, and heat-insulating PE film is 150 μm, and the preparation method is the same as that in Example 1.

[0134] The preparation methods of the three-layer high-buffering, anti-drop, and heat-insulating composite film and bag, and the four-layer high-buffering, anti-drop, and heat-insulating composite film and bag are the same as those in Example 1.

[0135] Comparative Example 1

[0136] The PE film of this comparative example is made of a co-extruded blown film of an outer layer, a middle layer and an inner layer, and the weight percentages of the materials of each layer among the three layers are: 30% for the outer layer, 40% for the middle layer, and 30% for the inner layer.

[0137] The manufacturers, properties and dosage of the raw materials for each layer are shown in Table 4.

[0138] Table 4 Manufacturers, properties and amounts (weight fractions) of the raw materials used in Comparative Example 1

[0139]

[0140] The preparation method of the above PE film is as follows: the raw materials of the outer layer, the middle layer and the inner layer are mixed in proportion by an automatic batching system, and then sent to the outer layer, the middle layer and the inner layer extruders; the raw materials of the outer layer, the middle layer and the inner layer are melted and plasticized and then sent to the die head for extrusion and film blowing; and then cooled by air cooling; and then passed through a stabilizing ring and a herringbone arrangement to the upper traction rotation to flatten the cylinder and enter the corona treatment device through a guide roller for corona treatment; and then the trimmed edges are passed through the lower traction clamp roller to enter the front and rear winding device for front and rear winding, and a 150 μm PE film can be obtained; the temperature and pressure of each zone of the extruder are shown in Table 5.

[0141] Table 5 Extruder temperature and pressure

[0142] temperature Zone 1 / ℃ Zone 2 / ℃ Zone 3 / ℃ Zone 4 / ℃ Zone 5 / ℃ Pressure / bar Outer Layer 160 165 170 160 160 215 Middle level 170 175 170 165 160 285 Inner Layer 168 172 165 160 160 320 Die head 185 190 185 180 / /

[0143] The preparation methods of the three-layer composite film and bag, and the four-layer composite film and bag are the same as those in Example 1, except that the high-buffering, anti-drop and heat-insulating PE film is replaced by the PE film prepared in Comparative Example 1.

[0144] Comparative Example 2

[0145] This comparative example is adjusted on the basis of Example 1. The amount of raw materials used in each layer is shown in Table 2. The weight percentages of the materials in each layer between the three layers are: 30% for the outer layer, 45% for the middle layer, and 25% for the inner layer; the total thickness of the PE film is 150 μm, and the preparation method is the same as that in Example 1.

[0146] The preparation methods of the three-layer structure composite film and bag, and the four-layer structure composite film and bag are the same as those in Example 1.

[0147] Comparative Example 3

[0148] This comparative example is adjusted on the basis of Example 3. The amount of raw materials used in each layer is shown in Table 2. The weight percentages of the materials in each layer among the three layers are: 20% for the outer layer, 55% for the middle layer, and 25% for the inner layer; the total thickness of the PE film is 150 μm, and the preparation method is the same as that in Example 1.

[0149] The preparation methods of the three-layer structure composite film and bag, and the four-layer structure composite film and bag are the same as those in Example 1.

[0150] Comparative Example 4

[0151] This comparative example is adjusted on the basis of Example 6. The amount of raw materials used in each layer is shown in Table 2. The weight percentages of the materials in each layer between the three layers are: 30% for the outer layer, 40% for the middle layer, and 30% for the inner layer; the total thickness of the PE film is 150μm, and the preparation method is the same as that in Example 1.

[0152] The preparation methods of the three-layer structure composite film and bag, and the four-layer structure composite film and bag are the same as those in Example 1.

[0153] Performance Testing:

[0154] 1. Mechanical properties and drop resistance test

[0155] The mechanical properties and density of the PE films prepared in Examples 1 to 8 and Comparative Examples 1 to 4 were tested. The test methods and test results are shown in Table 6.

[0156] The cushioning and anti-drop performance of the three-layer composite bags prepared in Examples 1 to 8 and Comparative Examples 1 to 4 was tested, and the test method was as follows: the composite film bag was filled with 1 kg of water, dropped from 1.5 meters, tested 5 times, and observed whether the bag was broken. The test results are shown in Table 6.

[0157] Table 6 Mechanical properties and drop resistance test results

[0158]

[0159]

[0160] According to the data in Table 1, it can be seen that the high-buffered anti-drop insulation PE film prepared by the present invention has low density, light weight, high tensile strength and elongation at break, and excellent mechanical properties; at the same time, after the composite film of the present invention is used to make a bag, it does not break after being dropped 5 times from a height of 1.5m with 1.5kg of water, indicating that it has excellent buffering performance and good anti-drop performance. Comparative Example 1 uses a conventional formula in the field to prepare a PE film without a foaming structure, and the resulting film has a large density and poor buffering performance; in Comparative Examples 2 to 4, the amount of foaming masterbatch is reduced, and the resulting PE film has a large density and poor buffering performance.

[0161] 2. Thermal insulation performance test

[0162] The thermal insulation performance of the three-layer composite bags prepared in Examples 1 to 8 and Comparative Examples 1 to 4 was tested, and the specific method was as follows: 150 mL of 85°C water was filled in the composite bag, and then placed in an environment of 23 to 25°C, and then the water temperature was tested every 30 minutes. The test results are shown in Table 7; 150 mL of water was frozen in a bag prepared by the composite film, and then placed in an environment of 23 to 25°C, and observed every 30 minutes to test the thawing time, and the results are shown in Table 8.

[0163] Table 7 Thermal insulation performance test results - hot water test / ℃

[0164]

[0165] Table 8 Thermal insulation performance test results - ice test

[0166]

[0167] It can be seen from the data in Tables 7 and 8 that the composite bag prepared by the present invention has high heat insulation and cold insulation properties, and the thawing and cooling time after being filled with cold drinks or hot drinks is extended by 3 to 4 hours compared with ordinary bags.

[0168] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high-buffered, anti-drop, heat-insulating PE film, characterized in that: The invention is made of a co-extruded blown film of an outer layer, a middle layer and an inner layer; at least one of the outer layer, the middle layer and the inner layer is a foaming structure.

2. The high-buffering, anti-drop, heat-insulating PE film according to claim 1, characterized in that: Among the outer layer, the middle layer and the inner layer, at least one layer is prepared from raw materials including foaming masterbatch; The melt index of the foaming masterbatch is 4-7 g / 10 min, and the density is 0.913-0.955 g / cm 3 .

3. The high-buffering, anti-drop, heat-insulating PE film according to claim 2, characterized in that: When only the raw materials for preparing the outer layer include foaming masterbatch, the mass of the foaming masterbatch is 2-8% of the total mass of the raw materials for preparing the outer layer; when only the raw materials for preparing the middle layer include foaming masterbatch, the mass of the foaming masterbatch is 1.5-8% of the total mass of the raw materials for preparing the middle layer; when only the raw materials for preparing the inner layer include foaming masterbatch, the mass of the foaming masterbatch is 2-6% of the total mass of the raw materials for preparing the inner layer; when any two layers of the outer layer, middle layer and inner layer contain foaming masterbatch, or all three layers contain foaming masterbatch, the mass of the foaming masterbatch in each layer is 1-11% of the total mass of the raw materials for preparing the layer.

4. The high-buffering, anti-drop, heat-insulating PE film according to claim 2 or 3, characterized in that: The model of the foaming masterbatch is CFE-3361G and / or FM10PE.

5. The high-buffering, anti-drop, heat-insulating PE film according to claim 1 or 3, characterized in that: The raw materials for preparing the outer layer include, by weight: 10 to 60 parts of low-density polyethylene, 20 to 80 parts of linear low-density polyethylene, 15 to 60 parts of metallocene low-density polyethylene, 0 to 8 parts of foaming masterbatch, and 0.5 to 1.5 parts of processing aid; The raw materials for preparing the middle layer include, by weight: 10 to 98 parts of low-density polyethylene, 0 to 8 parts of foaming masterbatch, and 0.5 to 1.5 parts of processing aid; The raw materials for preparing the inner layer include, by weight: 15 to 50 parts of low-density polyethylene, 20 to 80 parts of metallocene low-density polyethylene, 10 to 80 parts of linear low-density polyethylene, 0 to 8 parts of foaming masterbatch, and 0.5 to 1.5 parts of processing aid; In the raw materials for preparing the outer layer, the middle layer and the inner layer, the mass fractions of the foaming masterbatch are not all 0.

6. The high-buffering, anti-drop, heat-insulating PE film according to claim 5, characterized in that: The low-density polyethylene used in the outer layer has a melt index of 0.2-5 g / 10 min and a density of 0.920-0.935 g / cm 3 The outer layer adopts linear low-density polyethylene with a melt index of 0.3-3.5 g / 10 min and a density of 0.912-0.930 g / cm 3 The outer layer adopts a metallocene low-density polyethylene with a melt index of 0.5 to 2.5 g / 10 min and a density of 0.908 to 0.930 g / cm 3 ; The low-density polyethylene used in the middle layer has a melt index of 0.1-3.5 g / 10 min and a density of 0.920-0.940 g / cm 3 ; The low-density polyethylene used in the inner layer has a melt index of 0.3-3.5 g / 10 min and a density of 0.920-0.930 g / cm 3 The metallocene low-density polyethylene used in the inner layer has a melt index of 0.5-2 g / 10 min and a density of 0.91-0.92 g / cm 3 The linear low-density polyethylene used in the inner layer has a melt index of 1.5 to 2.5 g / 10 min and a density of 0.912 to 0.925 g / cm 3 ; The processing aids used in the outer layer, middle layer and inner layer have a melt index of 1.5-2.5 g / 10 min and a density of 0.910-0.925 g / cm 3 .

7. The method for preparing the high-buffering, anti-drop, and heat-insulating PE film according to any one of claims 1 to 6, characterized in that: The following steps are involved: The raw materials for the outer layer, the middle layer and the inner layer are subjected to three-layer co-extrusion blown film to obtain the high-buffering, anti-drop and heat-insulating PE film; among the raw materials for the outer layer, the middle layer and the inner layer, the raw materials for at least one layer include foaming masterbatch.

8. A composite membrane, characterized in that The composite film comprises a heat-insulating layer, and the heat-insulating layer is the high-buffering, anti-drop, and heat-insulating PE film according to any one of claims 1 to 6 or the high-buffering, anti-drop, and heat-insulating PE film prepared by the preparation method according to claim 7.

9. The composite membrane according to claim 8, characterized in that The composite film has a three-layer structure or a four-layer structure; the three-layer structure includes a printing layer, a barrier layer and a thermal insulation layer arranged in sequence; the four-layer structure includes a printing layer, a barrier layer, a thermal insulation layer and a PE heat sealing layer arranged in sequence; or, the four-layer structure includes a paper layer, a barrier layer, a printing layer and a thermal insulation layer arranged in sequence.

10. A composite bag, characterized in that: Prepared from the composite membrane described in claim 8 or 9.

Citation Information

Patent Citations

  • Foaming master batch and thickening type plastic film and corresponding preparation methods

    CN105504446A

  • Frozen storage food insulated bag

    CN206142079U

  • Method for manufacturing polyolefin multilayer film

    JP2002225108A